Bactericidal nanopatterns generated by block copolymer self-assembly - Fontelo, R. (2020)
We describe the bactericidal capacity of nanopatterned surfaces created by self-assembly of block copolymers. Distinct nanotopographies were generated by spin-coating with polystyrene-block-poly(2-vinylpyridine) (PS-b-P2VP) followed by solvent vapor annealing. We demonstrate that the bactericidal efficiency of the developed coatings depends on the morphology and the chemistry of the surface: cylindrical nanotopographies presenting both blocks at the surface have stronger bactericidal effect onÂ Escherichia coliÂ than micellar patterns with only PS exposed at the surface. The identified mechanism of bacterial death is a mechanical stress exerted by the nanostructures on the cell-wall. Moreover, the developed nanopatterns are not cytotoxic, which makes them an excellent option for coating of implantable materials and devices. The proposed approach represents an efficient tool in the fight against bacteria, which acts via compromising the bacterial wall integrity.